2012
DOI: 10.1093/ehjci/jes269
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve as a link between diastolic and systolic function and exercise capacity in heart failure

Abstract: In this group of heart failure patients, VO2 peak was correlated with CFR, E/e', and s' but not with traditional measures of systolic function. CFR remained associated with VO2 peak independently of diastolic and systolic function and is likely to be a limiting factor in functional capacity of heart failure patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
2
22
0
2
Order By: Relevance
“…This non-invasive measure of CFR has been validated against invasive measurements [43,44] and PET [45]. CFR is performed at our research unit with a low intra- and inter-observer variability and good repeatability [29,46]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This non-invasive measure of CFR has been validated against invasive measurements [43,44] and PET [45]. CFR is performed at our research unit with a low intra- and inter-observer variability and good repeatability [29,46]. …”
Section: Discussionmentioning
confidence: 99%
“…CFR has been shown to be a predictor of poor prognosis and mortality in patients with known or suspected CAD even when the coronary arteries were normal [27,28]. In CHF patients CFR has been shown to be positively correlated to VO 2 peak [29]. Exercise training has been shown to improve CFR in patients with CAD [30], while weight reduction following a multidisciplinary rehabilitation program resulted in improved CFR in overweight persons with no CAD [25].…”
Section: Introductionmentioning
confidence: 99%
“…Tschöpe et al measured CFR in patients with diastolic dysfunction, showing a reduced vasodilatory response to intracoronary acetylcholine infusion even before onset of HF symptoms [78]. Furthermore, invasively measured CFR is reduced in HFpEF patients and CFR correlates with echocardiographic measures of diastolic function and LV hypertrophy [76, 78, 79]. Interestingly, two studies in HFrEF patients showed no relationship between CFR and peripheral endothelial function [75, 80].…”
Section: Various Vascular Beds Display Endothelial Dysfunction In mentioning
confidence: 99%
“…As a result of these changes in coronary physiology, there is likely remodeling of the coronary arteries. This helps mitigate the effects of low oxygen diffusion and LV diastolic dysfunction that could result in susceptibility to myocardial ischemia 1,2,13 .…”
Section: Introductionmentioning
confidence: 99%